If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(r + -98) = -12 Reorder the terms: 6(-98 + r) = -12 (-98 * 6 + r * 6) = -12 (-588 + 6r) = -12 Solving -588 + 6r = -12 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '588' to each side of the equation. -588 + 588 + 6r = -12 + 588 Combine like terms: -588 + 588 = 0 0 + 6r = -12 + 588 6r = -12 + 588 Combine like terms: -12 + 588 = 576 6r = 576 Divide each side by '6'. r = 96 Simplifying r = 96
| 3z(2z+7)-12=0 | | 50-u=96 | | x+x-7=x+9+x+2+x-7 | | 4x+4=-3 | | 2+4x=9+10x | | 7y+2y+7=90 | | 2+4=9+10 | | 4m+2=34 | | 2x+4=9x+10 | | 2(5x+9)=10x+8 | | 3q^4-48=0 | | 5-v=-2 | | 2x+4x=9-10 | | -2(n-8)+-3=-7 | | -4-37=6y+13 | | 19-q=13 | | -20+4K=-5(4+4K)-5k | | (y/4)^2=49 | | x*x-14+x*x=x*x*x+9+2-7 | | -8-4p=-2p-16 | | 4(2X-5)=2(3X+6) | | 2-6m=-7m+1 | | x+5=E^2+kx+30 | | Z+2x=128 | | 120/x | | 9x/72x^@-9x | | 154=x^2+11x+28 | | 25k^2-36=0 | | x^2+4x+5=-2x | | 5y-11=69 | | 75x-15-6x-12=40x+55 | | 18x-6y=3 |